Design and characterization of electroactive gelatin methacrylate hydrogel incorporated with gold nanoparticles empowered with parahydroxybenzaldehyde and curcumin for advanced tissue engineering applications - Zahra Barabadi; Asrin Bahmani; Marzieh Jalalimonfared; Milad Ashrafizadeh; Morteza Rashtbar; Esmaeel Sharifi; Haili Tian (Journal of Materials Science: Materials in Medicine)
Abstract Electroconductive polymers are the materials of interest for the fabrication of electro-conductive tissues. Metal ions through the redox systems offer polymers with electrical conductivity. In this study, we processed a gelatin methacrylate (GelMA) network with gold nanoparticles (GNPs) through a redox system with parahydroxybenzaldehyde (PHB) or curcumin to enhance its electrical conductivity. Induction of the redox system with both PHB and curcumin into the GelMA, introduced some new functional groups into the polymeric network, as it has been confirmed by H-NMR and FTIR. These new bonds resulted in higher electro-conductivity when GNPs were added to the polymer. Higher electroactivity was achieved by PHB compared to the curcumin-induced redox system, and the addition of GNPs without redox system induction showed the lowest electroactivity. MTT was used to evaluate the biocompatibility of the resultant polymers, and the PHB-treated hydrogels showed higher proliferative effects on the cells. The findings of this study suggest that the introduction of a redox system by PHB in the GelMA network along with GNPs can contribute to the electrochemical properties of the material. This electroactivity can be advantageous for tissue engineering of electro-conductive tissues like cardiac and nervous tissues. Graphical Abstract